Sanksi Pidana Bagi Pelaku Pemalsuan Surat Rapid Test Di Kota Denpasar - Made Dwi Raditya Utama Putra Sari; A.A Ngurah Oka Yudistira Darmadi (International Forum of Researchers and Lecturers, 2023)
This study aims to identify and analyze the causes and legal consequences of falsifying a health certificate or a Rapid Test Covid-19 letter. This research is included in descriptive empirical research with data collection carried out through document studies and interviews, and is supported by primary legal materials in the form of applicable regulations and related to forgery of rapid test letters, secondary materials of law books and also legal journals related to forgery of letters rapid test. The data collected through research was analyzed qualitatively by arranging existing sentences so that they were easy to understand. The results of this study indicate that the factors that cause rapid test letter falsification are economic factors, time factors, factors of someone who wants to pass to travel outside the region, factors of intention and opportunity. The application of sanctions for perpetrators of crimes in the form of document forgery is generally regulated in the Criminal Code in Article 263 paragraph (1), so that criminal sanctions for perpetrators of forgery of rapid test letters are punishable by a maximum penalty of 6 (six) years in prison.